Elevated reactive oxygen species can drive the alternative lengthening of telomeres pathway in ATRX-null cancers - Goncalves, Tomas; Cunniffe, Siobhan; Ma, Tiffany S; Mattis, Natalie; Rose, Andrew W; Kent, Thomas; Mole, David R; Geiller, Helene E B; van Bijsterveldt, Linda; Humphrey, Timothy C; Hammond, Ester M; Gibbons, Richard J; et al. (Nucleic acids research, 2025)
The alternative lengthening of telomeres (ALT) pathway is a telomerase-independent mechanism for immortalization in cancer cells and is commonly activated in low-grade and high-grade glioma, as well as osteosarcoma. The ALT pathway can be activated under various conditions and has often been shown to include mutational loss of ATRX. However, this is insufficient in isolation and so other cellular event must also be implicated. It has been shown that excessive accumulation of DNA:RNA hybrid structures (R-loops) and/or formation of DNA–protein crosslinks (DPCs) can be other important driving factors. The underlying cellular events leading to R-loop and DPC formation in ALT cancer cells to date remain unclear. Here, we demonstrate that excessive cellular reactive oxygen species (ROS) is an important causative factor in the evolution of ALT-telomere maintenance in ATRX-deficient glioma. We identified three sources of elevated ROS in ALT-positive gliomas: co-mutation of SETD2, downregulation of DRG2, and hypoxic tumour microenvironment. We demonstrate that elevated ROS leads to accumulation of R-loops and, crucially, resolution of R-loops by the enzyme RNase H1 prevents ALT pathway activity in cells exposed to elevated ROS. Further, we found a possible causal link between the formation of R-loops and the accumulation of DPCs, in particular, formation of TOP1 complexes covalently linked to DNA (Top1cc). We also demonstrate that elevation of ROS can trigger over-activity of the ALT pathway in osteosarcoma and glioma cell lines, resulting in excessive DNA damage and cell death. This work presents important mechanistic insights into the endogenous origin of excessive R-loops and DPCs in ALT-positive cancers, as well as highlighting potential novel therapeutic approaches in these difficult-to-treat cancer types.